A happy valve in a happy patient? Serotonergic antidepressants and the risk of valvular heart disease (SERVAL). A case-control study. Issue 1 (2nd January 2016) - De Backer, Tine; Petrovic, Mirko; Audenaert, Kurt; Coeman, Mathieu; De Bacquer, Dirk
Abstract : Objectives : The objective was to investigate the risk of valvular heart disease in humans in relation to the use of selective serotonin reuptake inhibitors (SSRIs) and serotonin and noradrenaline reuptake inhibitors. Design: A case-control study. We conducted a case-control study within this cohort in which patients with newly diagnosed cardiac valve regurgitation were age-matched to controls. Patient demographics, their cardiovascular risk factors and medication use were extracted in both series. Use of SSRIs, serotonin and noradreline reuptake inhibitors (SNRIs) and other pro-serotonergic agents, their dose and treatment duration were recorded. Logistic regression analysis was used to establish the strength of the association between SSRI/SNRI use and valvular heart disease. Setting: Outpatient clinic of the cardiology department at the Ghent University Hospital, East-Flanders in Belgium. Participants: Total of 2911 persons 21–58 years of age who had undergone an echocardiogram in the period 2006–2010 and had no known cardiovascular disease or previous cardiac intervention. Two hundred and six echocardiographically proven cases of valvular regurgitation and 195 matched controls. Main outcome measure: Odd ratio of valvular disease associated with intake of serotonergic drugs. Results : Of the 206 patients with newly diagnosed cardiac valve regurgitation, 11.6% were exposed to serotonergic agents compared to 4.1% in the 195 control patients, leading to an odds ratio of 3.08 (95% confidence interval [CI] 1.35–7.04). The analysis of doses and treatment durations revealed a dose–relationship pattern between SSRI/SNRI use and prevalent valvular heart disease. Conclusions : In this study, use of serotonergic antidepressants was associated with an increased rate of valvular regurgitation in humans.